IMPLEMENTATION OF RESTITUTION FOR VICTIMS OF ABUSE ACCORDING TO INDONESIAN CRIMINAL LAW - Adamullah, Tubagus Alandaru; Fuqoha (Universitas Bengkulu, 2024)
This research primarily focuses on analyzing the concept of restitution in the context of victims of abuse, as well as identifying the challenges and benefits of implementing restitution in criminal law enforcement in Indonesia. The research employs a normative juridical method. The implementation of restitution for victims of abuse in Indonesia still faces various obstacles, such as a lack of understanding of the concept of restitution among law enforcement officials and a lack of awareness of victims' rights to receive restitution. However, there are also significant benefits from implementing restitution, such as providing compensation to victims for the losses they have suffered and strengthening restorative justice in the criminal justice system. This research provides an overview of the implementation of restitution for victims of abuse under Indonesian criminal law and offers recommendations to enhance the effectiveness and fairness in protecting victims' rights through the mechanism of restitution. Keywords: Criminal Law in Indonesia; Restitution; Victim.